2017
DOI: 10.1016/j.tranon.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Monocyte-to-Lymphocyte Ratio in Peripheral Blood Predicts Stages, Metastasis, and Histological Grades in Patients with Ovarian Cancer

Abstract: PURPOSE: The monocyte-to-lymphocyte ratio (MLR) has been shown to be associated with the prognosis of various solid tumors. This study sought to evaluate the important value of the MLR in ovarian cancer patients. METHODS: A total of 133 ovarian cancer patients and 43 normal controls were retrospectively reviewed. The patients' demographics were analyzed along with clinical and pathologic data. The counts of peripheral neutrophils, lymphocytes, monocytes, and platelets were collected and used to calculate the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 30 publications
(35 reference statements)
6
90
1
Order By: Relevance
“…Thus, the PLR might be an indicator of treatment response in dose-dense chemotherapy, and can help clinicians to decide when to switch patients to another chemotherapy regimen 27 . A study by Xiang and colleagues compared the MLR together with PLR between OC patients and controls; significant differences were observed 28 . In a study by Kokcu and colleagues, PLR increased progressively with increases in the stage of OC, indicating that it could function as an independent prognostic factor related to the cancer stage 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the PLR might be an indicator of treatment response in dose-dense chemotherapy, and can help clinicians to decide when to switch patients to another chemotherapy regimen 27 . A study by Xiang and colleagues compared the MLR together with PLR between OC patients and controls; significant differences were observed 28 . In a study by Kokcu and colleagues, PLR increased progressively with increases in the stage of OC, indicating that it could function as an independent prognostic factor related to the cancer stage 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response may be monitored through routine blood analysis. Peripheral blood leukocyte count is a simple and valuable indicator that can reflect the degree of systemic inflammatory response in tumor patients [20], and elevations of NLR, PLR, and MLR are thought to reflect an exaggerated systemic inflammatory response [6-8]. Asari et al [6] found that high PLR could be used as an independent prognostic risk factor in resectable pancreatic ductal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al [7] showed that NLR was an independent predictor for colon cancer patients. Xiang et al [8] reported that peripheral blood MLR before surgery could be a significant predictor of advanced stages, advanced pathologic grades, and positive lymphatic metastasis in ovarian cancer patients. Regarding the underlying mechanism, the tumor may cause nonspecific inflammation that leads to a change in leukocyte types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients whose monocyte to lymphocyte ratio was higher than 0/23 in compare with her which the ratio is lesser than 0/23 had higher serum levels of HE4, CA19-9 and CA125. There was significant difference in overall survival in two groups too [12]. In the study carried out by Barbo in 2015 in United States the role of leukocytosis and thrombocytosis has been reviewed on post operational complications and mortality rate.…”
Section: Discussionmentioning
confidence: 99%